2013
DOI: 10.3329/jdmc.v21i2.15299
|View full text |Cite
|
Sign up to set email alerts
|

Clinical CHaracteristics of Diabetic Ketoacidosis in Type 2 Diabetes Mellitus in Bangladesh Adult Patients

Abstract: J Dhaka Medical College, Vol. 21, No. 2, October, 2012, Page 131-139 DOI: http://dx.doi.org/10.3329/jdmc.v21i2.15299

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
2
0
3
Order By: Relevance
“…Outcome of this study showed that 6.5% patients expired in hospital. Almost similar results were found in two different reports from Bangladesh 4,20 . Outcome is variable, depends upon early diagnosis and onset of treatment, underlying causes and standards of care 11,13 .…”
Section: Discussionsupporting
confidence: 89%
“…Outcome of this study showed that 6.5% patients expired in hospital. Almost similar results were found in two different reports from Bangladesh 4,20 . Outcome is variable, depends upon early diagnosis and onset of treatment, underlying causes and standards of care 11,13 .…”
Section: Discussionsupporting
confidence: 89%
“…Le sexe masculin était prédominant dans notre étude (58,8%) avec un sex-ratio de 1,42. Cette prédominance du sexe masculin est rapportée par certains auteurs [ 10 – 14 ]; par contre d'autres rapportent une prédominance féminine [ 9 , 15 ]. Compte tenu de ces divergences, nous ne pouvons pas dire que l'acidocétose diabétique est plus l'apanage des hommes que des femmes.…”
Section: Discussionunclassified
“…En Algérie, Boutabia [ 19 ] retrouvait une prédominance des facteurs infectieux dans 51,7% des cas. Au Bangladesh, Hossain [ 10 ] constate qu'un patient sur deux n'adhérait pas au traitement. Le taux d'interruption thérapeutique dans l’étude de Randall varie entre 56 et 78% et la plupart de ces patients n'ont donné aucune raison d'arrêt d'insulinothérapie [ 11 ].…”
Section: Discussionunclassified
“…This scenario is common in local studies 4,5,12 as well as in international reports. 13,14 Precipitating causes of DKA were not different in this study from previous studies in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Precipitating causes of DKA were not different in this study from previous studies in Bangladesh. 4,5,12 Infection and non-compliance to anti-diabetic medications were common precipitants in the current study accounting for over three-fourth of cases. Almost similar picture was seen in different studies throughout the world.…”
Section: Discussionmentioning
confidence: 99%